The association of coronary artery disease with heart rate at anaerobic threshold and respiratory compensatory point - Kong, Yiya; Shen, Ruihuan; Xu, Tao; Zhou, Jihong; Xia, Chenxi; Zou, Tong; Wang, Fang (Frontiers in Cardiovascular Medicine, 2024)
Background There is limited knowledge regarding the association between heart rate (HR) during different exercise phases and coronary artery disease (CAD). This study aimed to evaluate the relationship between four exercise-related HR metrics detected by cardiopulmonary exercise testing (CPET) and CAD. These metrics include HR at the anaerobic threshold (HRAT), HR at respiratory compensatory point (HRRCP), maximal HR (HRmax), and HR 60 s post-exercise (HRRec60s). Methods The 705 participants included 383 with CAD and 322 without CAD in Beijing Hospital, who underwent CPET between January 2021 and December 2022. The Logistic regression analysis was applied to estimate the odds ratio and the 95% confidence interval. Additionally, the multivariable Logistic regression analyses with restricted cubic splines were conducted to characterize the dose-response association and explore whether the relationship was linear or nonlinear. Results Our primary finding indicates that for each one-beat increase in HRAT, there is a 2.8% reduction in the adjusted risk of CAD in the general population. Similarly, a one-beat increase in HRRCP corresponds to a 2.6% reduction in the adjusted risk of CAD. Subgroup analyses revealed significant interactions between HRAT and factors such as sex, hypertension, and lung cancer, as well as between HRRCP and sex and hypertension, in relation to CAD. The dose-response analysis further confirmed that higher HRAT and HRRCP are associated with a reduced risk of CAD. Conclusion These results are suggestive of a good association between HRAT, HRRCP, and CAD. The lower HRAT, and HRRCP are signs of poor HR response to exercise in CAD. HRAT and HRRCP are potentially good indicators of poor HR response to exercise without considering maximal effort.